The clinical value of screening for acetaminophen in all patients with intentional overdose or altered mental status suspected to be secondary to overdose - Alyahya, Bader; Alalshaikh, Abdulaziz; Almohawes, Mohammed; Alnowiser, Mosaed; Alsuliman, Omar; Alrefaei, Rand; Alaidarous, Sarah; Alnahdi, Maha; Tamur, Shadi; Alfaifi, Musa; Al Deeb, Mohammed; Al Aseri, Zohair A. (Frontiers in Pharmacology, 2025)
BackgroundAcetaminophen (APAP) is commonly coingested in cases of suicide or intoxication because it is widely available, effectively analgesic and antipyretic, and it is often combined with other medications, such as opioids and antihistamines. APAP overdose often causes no symptoms or nonspecific symptoms in the first 12–24 h after ingestion. Delayed diagnosis is associated with a reduced response to antidote and sometimes liver failure and mortality. However, ordering unnecessary test is not cost-effective specially if it is mostly negative, and empirical therapy is associated with significant cost and possible adverse effects.MethodsThis single-center retrospective study was conducted at King Saud University Medical City (KSUMC) in Riyadh, Saudi Arabia. Our population included all patients who presented to the emergency department with intentional drug overdose or altered mental status (AMS) suspected to be related to an overdose between June 2015 and January 2024 but with a history that was not suggestive of APAP overdose. Medical records were reviewed for patient information on demographic data, overdose details, and documentation of the clinical features of toxicity. All the subjects were kept anonymous; we used code numbers as identifiers. The data collected by the investigators were entered into an Excel worksheet in an encrypted format.ResultsA total of 2914 patients were screened for acetaminophen (APAP) levels and 1517 met our inclusion criteria. Fourteen (0.9%) patients had detectable levels (>10 μg/mL) despite a negative history. Three (0.2%) patients had levels above 100 μg/mL and were treated with N-acetylcysteine (NAC).ConclusionOur study revealed that a small number of patients who presented with intentional overdose but denied APAP ingestion or AMS suspected to be due to overdose had a positive APAP level. But, Given the serious consequences of APAP toxicity we cannot recommend stopping the screening for APAP specially in high-risk suicidal patients. A larger multicenter study is recommended to identify those high-risk patients. We also found deviation from the current guidelines regarding NAC administration in patients with positive APAP level when the time of ingestion is unknown.